A comparative study on the performance and efficiency of financial conglomerates and universal banks in the Philippines from years 2000 to 2007 - Balmes, Arvin M. (Animo Repository, 2009)
Due to the 1998 financial crisis the Philippne banking industry suffered. The Bangko Sentral ng PIlipinas (BSP) encourages financial institutions specifically bank to have merger and acquisition to expand their capital to improve efficiency and performance. Thus, this paper analyzes the cost efficiency and performance based on ROE, ROA, and net interest margin of Philippine financial conglomerates and universal banks. The researchers would like to find if conglomerates are cost efficient and have higher performance ratio than their competing universal banks. The output and cost of financial conglomerates and universal banks will be compared to indicate which one is more cost efficient and have higher performance in terms of ROA, ROE and net interest margin. It would also indicate if there is a need to encourage the financial institutions to provide services other than their traditional ones, such as the FC which offers a variety of financial services to their customers.